2021
DOI: 10.7759/cureus.18017
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Ketoacidosis: Possible Cause of Thrombotic Thrombocytopenic Purpura

Abstract: Acquired thrombotic thrombocytopenic purpura (TTP) is an uncommon microangiopathic disorder that can have variable presentations and can be precipitated by a multitude of stressors to the body, most commonly sepsis. TTP is caused by a deficiency of ADAMTS13 leading to intravascular clotting causing thrombocytopenia and microangiopathic hemolytic anemia. TTP can be associated with various other pathologic conditions. One such rare association has been reported with diabetic ketoacidosis (DKA). Here, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, several studies have reported a significant association between DKA and TMA, suggesting that the incidence of TMA in DKA may be higher than previously thought [ 4 ]. Jackson et al described a case of TTP in an old male triggered by new onset DKA [ 5 ]. After managing DKA and TTP simultaneously, his condition improved with the resolution of both TTP and DKA.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported a significant association between DKA and TMA, suggesting that the incidence of TMA in DKA may be higher than previously thought [ 4 ]. Jackson et al described a case of TTP in an old male triggered by new onset DKA [ 5 ]. After managing DKA and TTP simultaneously, his condition improved with the resolution of both TTP and DKA.…”
Section: Discussionmentioning
confidence: 99%